2022
DOI: 10.3390/vaccines10010087
|View full text |Cite
|
Sign up to set email alerts
|

Pyoderma Gangrenosum Induced by BNT162b2 COVID-19 Vaccine in a Healthy Adult

Abstract: (1) Background: Pyoderma gangrenosum (PG) is a rare neutrophilic dermatosis of unknown etiology. Coronavirus disease 2019 (COVID-19) vaccines can cause a variety of adverse cutaneous manifestations. PG associated with mRNA vaccines has not previously been described. This case study reports on the first patient to develop PG after receiving BNT162b2. (2) Case Presentation: An otherwise-healthy 27-year-old man developed multiple skin lesions 24 h after receiving the first dose of the messenger RNA-based Pfizer/B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…Not only AGEP but also SARS-CoV-2 vaccine-related dermatological manifestations have been reported in large studies. 44,45 While most are non-threatening skin reactions, a couple of severe cutaneous reactions following several SARS-CoV-2 vaccinations include Steven-Johnson's, 46,47 dermatomyositis, 48 IgA vasculitis, 49 pyoderma gangrenosum, 50 extensive rashes with blisterings, 51 TEM 52 and erythema multiforme, 53,54 and lupus erythematosus. 55 Our patient has developed AGEP probably due to terbinafine, as the skin rash occurred a few days after starting the drug.…”
Section: Discussionmentioning
confidence: 99%
“…Not only AGEP but also SARS-CoV-2 vaccine-related dermatological manifestations have been reported in large studies. 44,45 While most are non-threatening skin reactions, a couple of severe cutaneous reactions following several SARS-CoV-2 vaccinations include Steven-Johnson's, 46,47 dermatomyositis, 48 IgA vasculitis, 49 pyoderma gangrenosum, 50 extensive rashes with blisterings, 51 TEM 52 and erythema multiforme, 53,54 and lupus erythematosus. 55 Our patient has developed AGEP probably due to terbinafine, as the skin rash occurred a few days after starting the drug.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies over the past 2 years have reported skin side-effects after COVID-19 vaccination, including PG. 17 – 21 To the best of our knowledge, a PG ulcer triggered by COVID-19 vaccination in a patient with UC has not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…109 Pyoderma gangrenosum was yet another rare complication after Pfizer vaccination in a patient, which was diagnosed by epidermal neutrophilic infiltrate with epidermal and dermal edema, underlying superficial dermal necrosis, and characteristic undermining with extensive mixed inflammatory infiltration of the dermis and abscess formation and hemorrhagic foci in the absence of any positive cultures. 26,110 In other studies, postvaccination cutaneous thrombosis resulted in superficial ulcers with necrotic bases and microscopic studies on such lesions exhibited the presence of microthrombi within blood vessels, ischemic epidermis, and necrosis of subcutaneous tissue. 111,112 As well, flaccid and tense bullous eruption and mucosal erosions were reported in some studies.…”
Section: Othersmentioning
confidence: 93%